PELATIHAN ANALISIS LAPORAN KEUANGAN KEPADA SISWA-SISWI SMUN 20 TANGERANG - Rini Trihastuti; M Bintang Prajogi; Christian Kho (PROSIDING SERINA, 2021)
From the preliminary survey, we found problems where students at SMUN 20 TANGERANG had never received knowledge about how to analyze company’s financial statements. For that we will provide solutions in the form of training on financial statement analysis. The target we want to achieve in this training is so that after the training is held, students at SMUN 20 TANGERANG can understand the types of company financial reports and be able to analyze them in order to assess company performance. The method of implementation that we will use in the training consists of several steps. First, conduct a preliminary survey by conducting interviews with the school. Second, prepare the training module. Third, given the condition of the Covid-19 pandemic which is still ongoing today, we are conducting online training with Zoom media. Fourth, giving online quizes to find out how far the children understand the material that has been explained. We also asked students to fill out a questionnaire to rate their satisfaction with the training provided in the form of a Google Form. The output of this PKM activity is:  Publications in Serina II Untar 2021. Opini Untar and Posters at Research Week held by Tarumanagara University.